A method for producing superfine black tea powder with enhanced infusion and dispersion property. (1st January 2017) - Xiao, Weihua; Zhang, Yang; Fan, Chongxin; Han, Lujia
Highlights: Superfine black tea powder (BTP) was prepared with medium diameter 6.9 μm. Superfine BTP showed markedly fast infusion rates and high infusion yields. Superfine BTP has preferable dispersion stability as compared to coarsely ground BTPs. Homogenization and addition of stabilizers improved the dispersion properties. Abstract: Tea is rich in healthy components including polyphenols, caffeine, gallic acids, and others. Current technology of tea infusion and extraction leads to more than 40% soluble solids wasted in spent leaf. To increase the bioaccessibility of black tea, we report a method of pulverization treatments including general and superfine grinding to reduce the particle size. In comparison with coarsely ground black tea powders (BTPs), the superfine ground BTP with medium diameter 6.9 μm resulted in significant higher infusion yield of total polyphenols (TPP), caffeine, and water-soluble carbohydrate (WSC). The total water-soluble solids (WSS) of superfine BTP infusion increased markedly by twice due to the accelerated diffusion and enhanced solubility. High correlation between particle size and sedimentation ratio suggested improved dispersion stability of superfine BTP. The optimal dispersion of 0.1% superfine BTP in water was obtained by combination of homogenization and 0.08% CMC-Na formulation with 27.05% centrifugal sedimentation ratio.